Lessons from abroad: how can we achieve a socially just educational system?. Issue 3 (3rd July 2022) - Reay, Diane
ABSTRACT: This article draws on case studies from abroad to illustrate what to avoid and what to promote in the quest for a socially just educational system. It first looks at the range of goals different countries have pursued in relation to education. It then focuses more closely on policies in a range of European countries, that have inhibited or enabled greater educational equality, with a specific focus on England as a negative case study of what to avoid when pursuing greater educational equality. It concludes by drawing lessons from abroad to inform debates in Ireland around how to achieve greater social justice in education.